Development of social arithmetic teaching materials based on realistic mathematics education to facilitate mathematical reasoning skills - Wati, Desi Kurnia; Saragih, Sehatta; Suanto, Elfis (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
The Ministry of Education and Culture emphasizes the importance of mathematical reasoning; however, current student abilities in this area remain low due to limited independent learning, insufficient resources, and varied teaching approaches. To address these challenges, strategies such as Realistic Mathematics Education (RME) are crucial, necessitating the development of appropriate teaching materials. This research aimed to develop RME-based social arithmetic teaching materials using the 4-D model, which includes the stages of Define, Design, Development, and Dissemination. In the Define stage, researchers analyzed learner needs, learning outcomes, and relevant concepts, establishing clear learning objectives. The Design stage involved creating teaching materials through the compilation of tests, selection of media, formatting, and content design. During the Development stage, a formative evaluation was conducted, including expert assessments, one-on-one evaluations, and trials. The materials were validated with a score of 86.40%, classified as very valid. In limited trials, they received an average rating of 85.92%, classified as very practical, and in field trials, an average of 82.81%, classified as practical. In the Dissemination stage, the teaching materials were distributed to participating schools. The study concludes that RME-based social arithmetic materials effectively support the development of students' mathematical reasoning skills, meeting the criteria of validity and practicality.